Effect of donor acceptor substitution position on the electrical responsive properties of azulene system: a computational study. (18th July 2019) - Maity, Rakesh; Mandal, Debkumar; Misra, Ajay
ABSTRACT: Effect of donor–acceptor substitution position on the electrical responsive properties like polarisability, first hyper polarisability of donor–acceptor substituted azulene derivatives have been investigated using HF and Density functional theory with various hybrid functional and basis. It is observed that among the DFT methods, CAM-B3LYP hybrid functional with correlation consistent polarised triple-zeta, cc-pVTZ basis show less overestimated value of polarisability and first hyperpolarisability compare to other hybrid functional and it is again advantageous than HF with similar basis in term of its price and performance ratio. An apparent violation of minimum polarisability principle among the studied azulene derivatives are observed and it has been explain due to non-constancy of the potential functions upon substitution of donor (NMe2 ) and acceptor (NO2 ) groups at different position of azulene ring. Computed β av values are in accordance with the extent of charge transfer character of the azulene with a few exceptions. Position of donor and acceptor group at the five- and seven-member ring also play a big role in determining the electrical responsive parameter has been discussed. It is also observed that 2 and 6 carbon atom of azulene are highly sensitive towards donor acceptor substitution. GRAPHICAL ABSTRACT: